Предмет: Алгебра,
автор: АлёнкаМятная
1) Упростить
а)10√3-4√48-√75
б)(5√2-√18)*√2
в) (3-√2)^2
Ответы
Автор ответа:
0
а) 10√3-4√48-√75=10√3-4√(16*3)-√(25*3)=10√3-4√(4²*3)-√(5²*3)=10√3-4*4*√3-5√3=-11√3
б) (5√2-√18)√2 = ( 5√2- √(2*9)) √2 = (5√2 -3√2)*√2= 2√2*√2=4
в) (3-√2)²=9-2*3*√2+√2²=9-6√2+4=13-6√2
б) (5√2-√18)√2 = ( 5√2- √(2*9)) √2 = (5√2 -3√2)*√2= 2√2*√2=4
в) (3-√2)²=9-2*3*√2+√2²=9-6√2+4=13-6√2
Похожие вопросы
Предмет: Физика,
автор: ksenaagafonova76
Предмет: География,
автор: erab11
Предмет: Английский язык,
автор: eusupova936
Предмет: Химия,
автор: nastjafirsova3